Hvor præskriptiv er en deskriptiv ordbog? Hvor deskriptiv er en præskriptiv ordbog? - Bergenholtz, Henning; Bøgelund, Christina (LexicoNordica, 2002)
There is much uncertainty and confusion as to the real differences between prescriptive and descriptive dictionaries. In general, the majority of existing accounts can be summed up to this: Descriptive relates to the empirical basis; accordance between the empirical data and the dictionary is required. Prescriptive relates to the genuine purpose of the dictionary; the dictionary is meant to help with problems concerning text production and will thus affect usage. This asymmetrical understanding would imply prescriptive and descriptive in practise being false contrasts. Here, we suggest a more consistent terminology which allows for both the function of the dictionary and the relation of the dictionary to the empirical basis.